Mini Review: Various Processing of Organic Waste into Food Packaging - Nur Ichsan, Onne Akbar; Jannah, Syerina Raihatul; Robbani, Syi'fa (Journal of Food and Agricultural Product, 2025)
The presence of organic waste from both food and non-food products has been identified as a significant contributing factor to environmental pollution. Several processing methodologies have been employed for organic waste, including producing biogas, compost, animal feed, and recycling materials for use in packaging. The potential for processing organic waste into food packaging is also interesting. This study aims to provide a comprehensive overview of the types of organic waste that can be utilized as food packaging materials. The waste identified in various articles was then grouped according to the kind of packaging material, including: paper packaging, plastic packaging, film packaging, and active packaging. The findings were then reviewed and compared based on packaging testing parameters, including morphological analysis (SEM, FTIR), thickness, thermal stability, color index, physical properties (water activity, water content, water absorption capacity, water solubility), mechanical properties (tensile strength and elongation at break, antioxidant and antibacterial activity, and biodegradation assessment in soil. The study showed that food packaging made from food waste has excellent properties that make it flexible, non-toxic and naturally biodegradable. The study also showed that making food packaging from organic waste is relatively simple and can be done at a relatively low cost. Keywords: organic waste, paper packaging, film packaging, bioplastic, active packaging